Yellow Subretinal Lesions following Initiation of Antituberculosis Therapy in A Tubercular Choroidal Granuloma: A Sign of Paradoxical Worsening?. (2nd January 2022) - Arora, Atul; Katoch, Deeksha; Jain, Sahil; Singh, Simar Rajan; Gupta, Vishali
ABSTRACT: Purpose: To describe the presentation and management of atypical subretinal lesions following initiation of antitubercular therapy for a tubercular choroidal granuloma. Case report: An 18-year-old female was diagnosed with choroidal granuloma and shallow exudative retinal detachment in the left eye. Biopsy from a cervical lymph node was positive for tuberculosis. She was treated with antitubercular therapy (ATT) and oral steroids. After one week of therapy exudative detachment increased markedly and discrete yellowish-white subretinal lesions appeared first in the inferior periphery, then temporally and later involved the macula leading to a drop in visual acuity. A diagnosis of paradoxical worsening was considered and she was managed with a higher dose of oral corticosteroids, intravitreal methotrexate and intravitreal ranibizumab. The granuloma healed and the subretinal lesions as well as exudative detachment gradually resolved with improvement in visual acuity. Conclusion: Subretinal yellow-white lesions may develop as a paradoxical response to ATT.